PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Galih Fristyan Hardias Tama; Rismansyah Rismansyah; Tri Sinarti (Management Insight: Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of capital structure and company size either simultaneously or partially on profitability in banking companies listed on the Indonesian stock exchange in 2015-2019. The sample of this research is 10 banking companies with sampling method using purposive sampling technique. In this study, the researchers used data analysis techniques including the classical assumption test, data analysis using the SPSS version 21 application. The results in this study indicate that the capital structure of banking companies listed on the Indonesia Stock Exchange in 2015-2019 has a significant effect on profitability. The results of the study also explain that banking companies listed on the Indonesia Stock Exchange in 2015-2019 have a significant effect on profitability. Capital structure and company size in banking companies listed on the Indonesia Stock Exchange in 2015-2019 together have a significant effect on profitability.